SAT0258 Disease related characteristics do not influence willingness to participate in a large clinical trial in rheumatoid arthritis (ra). (1st June 2001) - De Jong, Z; Munneke, M; Jansen, A; Vlieland, TP Vliet; Hazes, JM
Abstract : Background: A major problem in the incorporation of results from clinical trials in daily practice is that demographic and clinical characteristics of patients who participate in clinical trials differ significantly from those of non-participants. It is not known if this limited generalizability of trial results is also present in trials with RA patients. Objectives: To investigate whether demographic or clinical characteristics of RA patients are a barrier to participation in a trial. In order to detect such an effect we investigated the recruitment of RA patients for a trial on the effectiveness of a long-term high intensity weight-bearing exercise programme. Methods: Medical records of all known RA patients from four cooperating centres were screened for eligibility (ARA 1987 revised criteria, 20–70 years, ACR functional class I-III, stable DMARD in the past 3 months, no prosthesis of a weight bearing joint, no serious comorbidity). Eligible patients received extensive written information and were invited for an information meeting. The investigators subsequently screened all patients who wished to participate to ensure the eligibility and a personalised approach. Participants as well as non-participants were mailed a questionnaire containing questions on socio-demographic and disease-related characteristics, comorbidity and experience with participation in clinical trials in the past. Questionnaires concerning functional status (HAQ), utility (EuroQol) and quality of life (RAQol) were added. Differences between participants and non-participants were tested with Mann-Whitney test or Chi-square test where appropriate. Results: 299 of the 300 participants (99.7%) and 892 of the 1191 non-participants (74.9%) returned the questionnaires completed. Participants were younger (median 54 vs. 57 yrs, p < 0.005), more often female (79 vs. 73%, p < 0.05) and the disease duration was slightly shorter (median 6 vs. 8 yrs, p < . 005). Participants and non-participants did not differ with respect to the presence of rheumatoid factor and erosions, previous and current use of medication, perception of burden of illness, comorbidity, experience with participation in clinical trials in the past, functional status, utility, and quality of life measures. Conclusion: Disease related characteristics do not influence the willingness to participate in a clinical trial on the effect of long-term high intensity exercise therapy. The slight differences in sociodemographic characteristics between participants and non-participants do not seem clinically relevant. The recruitment strategy in which all eligible patients were approached in a non-selective, unbiased way may have contributed to this favourable result.